In the corporate backstage, the taste of revenge: Misbehaviour and humor as form of resistance and subversion - Medeiros, Cíntia Rodrigues de Oliveira (2016)
Recently, several cases of employees of corporations that have adopted an improper attitude toward clients were released, indicating that these events are common, not rare. In this article, we interviewed officials and former employees of fast-food and call centers in order to meet their narratives about the corporate scenes, focusing on the literature on misbehaviour and humor as a form of resistance in organizations. Our analysis points to two main narratives: revenge is a dish best served cold; and the customer is not king.